The Impact of Implementing Corporate Social Responsibility (CSR) on Company Financial Performance - Sylvanda Aprilia Divara; Rizal Arsy Asy Rohman; Hwihanus Hwihanus (International Journal of Economics, Management and Accounting, 2024)
Study This aim For know impact application of Corporate Social Responsibility (CSR) to the Company's Financial Performance by method compare or use meta- analysis method from a number of journal international with topic The impact of Corporate Social Responsibility(CSR) on Financial Performance . The results we got from journals the there is difference results or opinion as well as variables used , there are positive , negative correlation​ or No There is correlation about impact Corporate Social Responsibility(CSR) to performance finance . Corporate Social Responsibility itself that is form not quite enough answer company to environment social must​ carried out by the company , meanwhile performance finance is a description of the condition finance company or ability company in manage finance company.